Taxonomy of Aristeidae (Dendrobranchiata:Penaeoidea) from the central coast of Brazil, collected by the Revizee program, between 19º and 22ºS - Tavares, Carolina R.; Serejo, Cristiana S. (Zootaxa, 2007)
The Aristeidae is a predominantly deep-water family composed of 26 species in nine genera. Until now, only four species were recorded from off the Brazilian coast: Aristaeomorpha folicea, Aristaeopsis edwarsiana, Aristeus antillensis and Hepomadus tener. With the material examined herein, another five species were recorded and redescribed from off the Brazilian coast: Aristeus antennatus, Hemipenaeus carpenteri, Plesiopenaeus armatus and Plesiopenaeus coruscans. In this paper these eight species are fully redescribed. Comments on geographical distribution and a key with the eight species found in the Brazilian waters are provided.